Gout, Hyperuricemia, and Crystal‐Associated Disease Network Consensus Statement Regarding Labels and Definitions for Disease Elements in Gout. Issue 3 (28th February 2019) - Bursill, David; Taylor, William J.; Terkeltaub, Robert; Kuwabara, Masanari; Merriman, Tony R.; Grainger, Rebecca; Pineda, Carlos; Louthrenoo, Worawit; Edwards, N. Lawrence; Andrés, Mariano; Vargas‐Santos, Ana Beatriz; Roddy, Edward; et al.
Abstract : Objective: The language currently used to describe gout lacks standardization. The aim of this project was to develop a consensus statement on the labels and definitions used to describe the basic disease elements of gout. Methods: Experts in gout (n = 130) were invited to participate in a Delphi exercise and face‐to‐face consensus meeting to reach consensus on the labeling and definitions for the basic disease elements of gout. Disease elements and labels in current use were derived from a content analysis of the contemporary medical literature, and the results of this analysis were used for item selection in the Delphi exercise and face‐to‐face consensus meeting. Results: There were 51 respondents to the Delphi exercise and 30 attendees at the face‐to‐face meeting. Consensus agreement (≥80%) was achieved for the labels of 8 disease elements through the Delphi exercise; the remaining 3 labels reached consensus agreement through the face‐to‐face consensus meeting. The agreed labels were monosodium urate crystals, urate, hyperuric(a)emia, tophus, subcutaneous tophus, gout flare, intercritical gout, chronic gouty arthritis, imaging evidence of monosodium urate crystal deposition, gouty bone erosion, and podagra. Participants at the face‐to‐face meeting achieved consensus agreement for the definitions of all 11 elements and a recommendation that the label "chronic gout" should not be used. Conclusion: Consensus agreement was achieved for the labels and definitions of 11 elements representing the fundamental components of gout etiology, pathophysiology, and clinical presentation. The Gout, Hyperuricemia, and Crystal‐Associated Disease Network recommends the use of these labels when describing the basic disease elements of gout.